RELATIONSHIP OF PERCEIVED PARENTAL BEHAVIOR WITH PROSOCIAL BEHAVIOR AND DIFFICULTIES IN ADOLESCENTS - Sánchez-Caicedo, Adriana (2024)
The research that led to this article aimed to relate the perceived parental behavior with prosocial behavior and difficulties in adolescents from Simón Bolívar, Ecuador. It was carried out using a postpositivist paradigm, a quantitative approach, non-experimental design, and cross-sectional, with correlational analysis. The sample consisted of 343 adolescents aged between 12 and 16 years selected by non-probabilistic convenience sampling with inclusion criteria. The instruments analyzed were the Strengths and Difficulties Questionnaire (SDQ) as well as the Children's Perceived Parental Behavior Questionnaire – Abbreviated (CRPBI-A). The analysis showed a predominance of normal levels for prosocial behavior (85.1%) and difficulties (68.29%), high levels for paternal overprotective style (78.7%), paternal communicative (77.8%), maternal communicative (81.0%) and maternal overprotective style (77. 8%). Furthermore, it is evident that there is a significant relationship between perceived parental behavior with prosocial behavior and difficulties in adolescents, highlighting the practical implications for parents, educators, and policymakers.